1993
DOI: 10.1128/iai.61.12.5374-5380.1993
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella typhimurium delta aroA delta aroD mutants expressing a foreign recombinant protein induce specific major histocompatibility complex class I-restricted cytotoxic T lymphocytes in mice

Abstract: Recombinant Salmonella typhimurium aroA aroD mutants which expressed ovalbumin were constructed. The two expression constructs used were based on either pUC18 or pBR322. The pBR322-based construct was more stable in vitro and in vivo than the pUC-based construct. Salmonellae containing the stable pBR322-based plasmid induced major histocompatibility complex (MHC) class I-restricted cytotoxic T lymphocytes (CTL), in contrast to salmonellae containing the pUC18-based expression construct. The priming of MHC clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…This strain induced the highest levels of B cell immunogenicity (Table 4 and Figures 2B, 3 and 4). This result is similar to those reported in previous studies, which have found that lowering the plasmid copy number results in enhanced plasmid stability and a reduction in the expression levels of heterologous antigens to non-toxic levels [31][32][33][34].…”
Section: B Cell Responses and Soluble Antigen Expression Levelssupporting
confidence: 92%
“…This strain induced the highest levels of B cell immunogenicity (Table 4 and Figures 2B, 3 and 4). This result is similar to those reported in previous studies, which have found that lowering the plasmid copy number results in enhanced plasmid stability and a reduction in the expression levels of heterologous antigens to non-toxic levels [31][32][33][34].…”
Section: B Cell Responses and Soluble Antigen Expression Levelssupporting
confidence: 92%
“…The pIC20H plasmid, which is derived from pUC19, has the highest copy number of the plasmids tested and it is possible that the increased copy number may have contributed to the plasmid's instability. A relationship between plasmid instability and the copy number has been observed in previous studies [24,31]. Turner et al [31] reported that ovalbumin expressed from a high-copy-number plasmid delivered by attenuated S. typhimurium was unable to induce ova-speci¢c cytotoxic T lymphocytes (CTLs) whereas the same antigen encoded on a lowercopy-number plasmid induced CTLs.…”
Section: Discussionmentioning
confidence: 80%
“…The titre of antibody present in mouse sera were determined using a standard endpoint ELISA. Immunoplates (Nunc A/S, Kamstrup, Denmark) were either coated with 10 Wg ml 31 S. typhimurium lipopolysaccharide (LPS ; Sigma, St Louis, MO, USA) in PBS, or 2 Lf (£occulating units) ml 31 tetanus toxoid (CSL Ltd, Parkville, Vic., Australia) in carbonate coating bu¡er (pH 9.6). Bound antibody was detected by adding sheep anti-mouse immunoglobulin (Ig) HRP conjugate (Silenus Laboratories, Hawthorn, Vic., Australia).…”
Section: Measurement Of Antibody Response By Enzyme-linked Immunosorbmentioning
confidence: 99%
“…Stable expression of antigen gene is extremely important for oral vaccine using attenuated Salmonella, as it relates to whether it could constantly effectively stimulate the body to produce an immune response. Studies affirmed that stability of plasmid might be relevant to the plasmid copy number [6], and ovalbumin expressed by an attenuated Salmonella harboring a low-copy number plasmid could stimulate to produce specific anti-ovalbumin (CTLs reaction) when carrying a high-copy number plasmid cannot [29]. In order to enhance plasmid stability during immunization, antibiotics were injected into the mice with the period of immunity, yet the result revealed that it is not practical to get the plasmids enhanced in vivo by this method [27].…”
Section: Discussionmentioning
confidence: 99%